Molecular aspects of skin ageing - Rocquet, C... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2002)
As our body's envelope, the skin acts as a biosensor with the environment and reflects our personality. Skin ageing is therefore an important and interesting topic of study. It results from the combination of intrinsic ageing and photoageing, which is due to the environmental influence, such as reactive oxygen species (ROS). The more recent data are gathered here to remind current knowledge about skin ageing, from a molecular level to the clinical signs, wrinkles and spots mainly. Because knowledge of the preferential biological targets of ageing has recently been making progress, it is possible to delay the manifestation of ageing, by acting on key biological processes.
Keywords: Beljakovine; Biosynthesis; Dna Damage; DNA mitohondrijska; DNA poškodba; Dna, Mitochondrial; Drug Effects; Genetics; Glikozilacijski končni produkti, napredni; Glycosylation End Products, Advanced; Kisik, aktivne oblike; Koža, staranje; Metalloproteinases; Oksidativni stres; Oxidative Stress; Protease Inhibitors; Proteazni inhibitorji; Proteins; Reactive Oxygen Species; Skin Aging; Telomerase; Telomeraza